2017
DOI: 10.1016/j.prnil.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of silodosin in the treatment of lower urinary tract symptoms in elderly men taking antihypertensive medications

Abstract: BackgroundBoth hypertension and lower urinary tract symptoms (LUTS) are common conditions in the elderly population. This study investigated the efficacy and safety of silodosin in the treatment of LUTS in elderly men who were taking antihypertensive medications.MethodsThis is an observational study which collected the medical records of patients who started silodosin medication for their LUTS between April 2015 and December 2015. Inclusion criteria were age ≥ 65 years, currently taking antihypertensive medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A notable finding in this study was that adding silodosin to treatment in individuals who already had orthostatic hypotension did not worsen the condition, but rather showed improvement in 2 patients. 66 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable finding in this study was that adding silodosin to treatment in individuals who already had orthostatic hypotension did not worsen the condition, but rather showed improvement in 2 patients. 66 …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, silodosin has shown to be effective and safe for management of LUTS in elderly patients taking antihypertensive medications. 66 It is speculated that due to the high uroselectivity for α 1β adrenergic receptors is mainly responsible for controlling BP enabling silodosin to have minimum effects on CV system. Silodosin has demonstrated promising results in increasing the probability of successful TWOC in patients with AUR and those taking antihypertensive drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silodosin has been found safe and effective for management of LUTS in patients who were taking antihypertensive medicines. 44 Silodosin has minimal cardiovascular effects due to its highly selectivity. 45,46 Silodosin proved a 583-fold selectivity for the α1A versus α1B subtype and 56-fold selectivity for the α1A versus α1D.…”
Section: Cardiovascular Advantages Of Silodosinmentioning
confidence: 99%
“…There have been several meta-analyses examining the effects of alpha blockers on AUR, with most studies suggesting that alpha blockers can increase the success rates of TWOC with a low incidence of adverse effects. 3 , 7 , 8 , 9 , 10 However, Zeif et al. 11 reported that there is limited evidence available indicating that alpha blockers can increase the success rate of TWOC.…”
Section: Introductionmentioning
confidence: 99%